Legal Protection Against Patients who Experience Overdose - Muslimah; Ta’adi; Diana Pujiningsih; Andi Wahyuddin Nur; Mawardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Overdose is a serious condition that occurs due to consuming excessive amounts of a drug or substance, which can be life-threatening. Legal protection for patients who experience an overdose is very important, especially related to patient rights, responsibilities of medical personnel, and health policies. According to WHO (World Health Organization), overdose is the use of psychoactive substances in dangerous amounts, which results in adverse effects, including death. Legal protection of patients who have overdosed is essential to ensure that they receive necessary treatment without fear of legal consequences. By upholding patient rights, medical personnel responsibilities, and supportive health policies, we can reduce the impact of overdoses and improve health outcomes for at-risk individuals. Collaboration between the government, health service providers, and the community is needed to create a safe environment for patients and their families.